2006
DOI: 10.1091/mbc.e05-08-0798
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Tumor Suppressor Homologue Sro7p Is Required for Targeting of the Sodium Pumping ATPase to the Cell Surface

Abstract: The SRO7/SOP1 encoded tumor suppressor homologue of Saccharomyces cerevisiae is required for maintenance of ion homeostasis in cells exposed to NaCl stress. Here we show that the NaCl sensitivity of the sro7⌬ mutant is due to defective sorting of Ena1p, the main sodium pump in yeast. On exposure of sro7⌬ mutants to NaCl stress, Ena1p fails to be targeted to the cell surface, but is instead routed to the vacuole for degradation via the multivesicular endosome pathway. SRO7-deficient mutants accumulate post-Golg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 76 publications
4
28
2
Order By: Relevance
“…The effect of loss of the Rab proteins on plasma membrane traffic of the markers was assessed after growth of the cells to log phase at 30°C. the plasma membrane localization of the sodium transporter Ena1p under high-salt stress (Larsson et al, 1998;Wadskog et al, 2006). Our findings, however, show a differential requirement under normal growth conditions.…”
Section: Discussioncontrasting
confidence: 49%
“…The effect of loss of the Rab proteins on plasma membrane traffic of the markers was assessed after growth of the cells to log phase at 30°C. the plasma membrane localization of the sodium transporter Ena1p under high-salt stress (Larsson et al, 1998;Wadskog et al, 2006). Our findings, however, show a differential requirement under normal growth conditions.…”
Section: Discussioncontrasting
confidence: 49%
“…The centromeric plasmid pUG35 (Niedenthal et al, 1996) and pUG35-ENA1 were kindly provided by Lennart Adler (Wadskog et al, 2006) (a gift from Martha Cyert and Victoria Heath).…”
Section: Methodsmentioning
confidence: 99%
“…Localization at the cell membrane has been demonstrated for S. cerevisiae Pmr2a/Ena1 and Pmr2b/Ena2 (94) and for S. occidentalis (7), although it has been reported that overexpression of ENA1 also results in the presence of the protein in intracellular membrane structures (11). Interestingly, SRO7/ SOP1, a homolog of the Drosophila Lgl tumor suppressor gene, encoding a protein involved in exocytic docking and fusion of Golgi apparatus-derived vesicles with the plasma membrane, was recently identified as being required for appropriate delivery of Ena1 to the plasma membrane (93). It is remarkable that the role of Sro7 could be relatively specific, since sensitivity to NaCl is the only evident phenotype of sro7 cells (45) and other membrane-directed proteins do not present altered membrane targeting (93).…”
Section: Gene Structure Functional Roles and Subcellular Localizationmentioning
confidence: 99%
“…Interestingly, SRO7/ SOP1, a homolog of the Drosophila Lgl tumor suppressor gene, encoding a protein involved in exocytic docking and fusion of Golgi apparatus-derived vesicles with the plasma membrane, was recently identified as being required for appropriate delivery of Ena1 to the plasma membrane (93). It is remarkable that the role of Sro7 could be relatively specific, since sensitivity to NaCl is the only evident phenotype of sro7 cells (45) and other membrane-directed proteins do not present altered membrane targeting (93).…”
Section: Gene Structure Functional Roles and Subcellular Localizationmentioning
confidence: 99%